Optimasi Platform Digital sebagai Transformasi Pendidikan Islam Berkemajuan - Salsabila, Unik Hanifah; Perwitasari, Anggie; Amadea, Neysa Salsabila Felasufa; Khasanah, Khusnul; Afisya, Bellafia (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2022)
Abstract Advances in technology and information help people develop their abilities in dealing with the current Covid-19 pandemic. Digital transformation in the world of education is the main trigger for student learning motivation and educators can utilize their digital skills to innovate in developing learning materials in schools. This journal uses a method in the form of a qualitative approach to literature study. The data we collect is obtained through data identification, reading, understanding, discussing data, presenting and drawing conclusions seeking and collecting sources from books and relevant journals. So researchers will find and understand the problems taken regarding how to optimize digital platforms with the transformation into progressive Islamic education. The results of this study indicate that digital transformation as a form of realization of progressive Islamic education provides a new direction for every community's life to be able to use it as well as possible so that it is not misused. Therefore, people need to equip themselves with education. Good use of digital and optimizing digital media platforms is important as an educational alternative to developing learning so that it is interesting, effective, and up to date. Microsoft Office 365 Zenius, Zoom, Google for Education, Whatsapp, Smart class are examples of platforms that can help optimize digital media in the renewal of advanced Islamic education. Keywords: Digital platforms; Transformation; Islamic education; progress. AbstrakKemajuan teknologi dan informasi membantu masyarakat mengembangkan kemampuannya dalam menghadapi pandemi Covid-19 saat ini. Transformasi digital di dunia pendidikan menjadi pemicu utama motivasi belajar peserta didik dan tenaga pendidik dapat memanfaatkan keterampilan digital mereka untuk berinovasi dalam mengembangkan bahan pembelajaran di sekolah. Jurnal ini menggunakan metode berupa pendekatan kualitatif studi pustaka. Data yang kami kumpulkan didapatkan melalui identifikasi data dengan, membaca, memahami, membahas data, menyajikan serta penarikan kesimpulan mencari dan mengumpulkan sumber dari buku dan jurnal-jurnal yang relevan. Jadi peneliti akan menemukan dan memahami permasalahan yang diambil mengenai bagaimana mengoptimalkan platform digital dengan adanya transformasi kedalam pendidikan Islam berkemajuan. Hasil penelitian ini menunjukkan bahwa transformasi digital sebagai bentuk realisasi pendidikan Islam berkemajuan, memberikan arah baru bagi setiap kehidupan masyarakat untuk dapat menggunakannya dengan sebaik mungkin agar tidak salah guna. Oleh sebab itu, masyarakat perlu membekali dirinya dengan edukasi. Penggunaan digital yang baik dan mengoptimalkan media platform digital menjadi penting sebagai alternatif pendidikan untuk mengembangkan pembelajarannya agar menarik, efektif, dan kekinian. Microsoft Office 365, Zenius, Zoom, Google for Education, Whatsapp, Smart class merupakan contoh platform yang dapat membantu mengoptimalkam media digital dalam pembaharuan pendidikan Islam berkemajuan. Kata Kunci: Platform digital; Transformasi; Pendidikan Islam; Berkemajuan.